Long reach cantilevers for sub-cellular force measurements - Paneru, Govind; Thapa, Prem S.; McBride, Sean P.; Ramm, Adam; Law, Bruce M.; Flanders, Bret N. (My University, 2012)
Maneuverable, high aspect ratio poly 3-4 ethylene dioxythiophene (PEDOT) fibers are fabricated for use as cellular force probes that can interface with individual pseudopod adhesive contact sites without forming unintentional secondary contacts to the cell. The straight fibers have lengths between 5 and 40 μm and spring constants in the 0.07–23.2 nN μmˉ¹ range. The spring constants of these fibers were measured directly using an atomic force microscope (AFM). These AFM measurements corroborate determinations based on the transverse vibrational resonance frequencies of the fibers, which is a more convenient method. These fibers are employed to characterize the time dependent forces exerted at adhesive contacts between apical pseudopods of highly migratory D. discoideum cells and the PEDOT fibers, finding an average terminal force of 3.1± 2.7 nN and lifetime of 23.4 ± 18.5 s to be associated with these contacts.